Kursus Singkat Monitoring Perkembangan Balita Dalam Penanganan Stunting Sebagai Upaya Peningkatan Pengetahuan Kader Surabaya Hebat - Inawati Inawati; Titiek Sunaryati; Harman Agusaputra; Putu Oky Ari Tania (Journal of Community Development, 2024)
Undernutrition is responsible for nearly 50% child deaths, especially in poor countries. Approximately 25% of toddlers worldwide experience stunted which is associated with mortality, cognitive impairment and reduced productivity. The mission of the Kementrian Kesehatan is to improve the level of public health through community empowerment (Posyandu). especially in Surabaya with the empowerment of Kader Surabaya Hebat (KSH). Wonokromo District, with an area of ​​8.42 Km2 and occupying 2.55% of the area of ​​Surabaya city, has 3 access to primary health facilities, covering 6 sub-districts (Kelurahan). The ratio of community health centers per Wonokromo sub-district is 1.9, this shows that the coverage of primary health access in Wonokromo is quite good. KSH knowledge needs to be improved through education, short courses and monitoring. The aim of this Pengabdian  activity is to increase knowledge regarding monitoring the toddlers development, especially in handling stunting toddlers. This activity was able to increase the knowledge of KSH as shown by an increase in the highest score of 100, from 10% to 54.2%. Increasing KSH knowledge is a first step so that it can be applied to the community, namely toddlers in the Wonokromo health center area, so that monitoring of stunting toddlers can run and can prevent or even reduce the stunting rate in Wonokromo.